2022
DOI: 10.1155/2022/1740295
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Valuable Role of ARMC1 in Invasive Breast Cancer as a Novel Biomarker

Abstract: Background. Invasive breast carcinoma (BRCA) is a common type of breast cancer with a high clinical incidence. Thus, it is significant to find effective biomarkers for BRCA diagnosis and treatment. Although some members of armadillo (ARM) repeat family of proteins are confirmed to be biomarkers in cancers, the role of armadillo repeat-containing 1 (ARMC1) in BRCA remains unknown. Methods. We firstly analyzed the ARMC1 expression in normal breast tissues and BRCA samples and its association with overall surviva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%